Integrated marketing communication: What are the barriers to integration? - Archer, Catherine (University of Western Sydney, 2008)
It is generally accepted within mainstream marketing circles that integrated marketing communication (IMC) is a desired state within organisations. This is despite the fact that, as in many areas of marketing discourse, there is still no clear accepted definition of IMC. In recent years, some scholars have argued, rather controversially, that in this post-modern world, integration of marketing communication is impossible (Christensen, Torp & Firat 2005). This paper, through a case study of a major Australian health care organisation, reviews the struggles to integrate communications, not just in a narrow marketing sense, but across the organisation. This paper offers new insights into the reality of implementing communication programmes in complex organisations and highlights the key barriers to integration of marketing communications faced by organisations.